Dmytro A. Yushchenko. Issue 37 (2nd October 2018) - Unknown
Abstract: "The Yushchenko group is interested in the development of (bio)chemical tools to study the biology of amyloidogenic proteins and lipid‐mediated cell signaling." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800524 . Abstract : "The Yushchenko group is interested in the development of (bio)chemical tools to study the biology of amyloidogenic proteins and lipid‐mediated cell signaling." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800524 .